Food Stock Analysis with the Utilization of the Single Moving Average Method - Febrianti, Intan; Hambali, Hambali; Sena, Maulana Dwi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
A grocery store is a store that sells daily necessities. Nine basic ingredients or better known as basic necessities are the type of business that anyone needs. The community needs a grocery store that sells daily necessities at affordable prices and close to the neighborhood. Sahriul Grosir is a business engaged in the sale of rice where uncertain demand makes this business to determine the stock for the following month. This research aims to implement the single moving average method for rice stock forecasting to support proper decision making. By using historical sales data from January 2024 to January 2025 to forecast the next 6 months. Forecasting results for the next 6 months, from February 2025 to July 2025. With a forecasting value obtained of 223, MAD value of 23.32, MSE value of 1203.20 and MAPE value of 9.43.